First clinical implementation of insertion force measurement in cochlear implantation surgery - Rau, Thomas S.; Böttcher-Rebmann, Georg; Schell, Viktor; Cramer, Jakob; Artukarslan, Eralp; Baier, Claas; Lenarz, Thomas; Salcher, Rolf (Frontiers in Neurology, 2024)
Purpose The significance of atraumatic electrode array (EA) insertion in cochlear implant (CI) surgery is widely acknowledged, with consensus that forces due to EA insertion are directly correlated with insertion trauma. Unfortunately, the manual perception of these forces through haptic feedback is inherently limited, and techniques for in vivo force measurements to monitor the insertion are not yet available. Addressing this gap, we developed of a force-sensitive insertion tool capable of capturing real-time insertion forces during standard CI surgery. Methods This paper describes the tool and its pioneering application in a clinical setting and reports initial findings from an ongoing clinical study. Data and experiences from five patients have been evaluated so far, including force profiles of four patients. Results The initial intraoperative experiences are promising, with successful integration into the conventional workflow. Feasibility of in vivo insertion force measurement and practicability of the tool’s intraoperative use could be demonstrated. The recorded in vivo insertion forces show the expected rise with increasing insertion depth. Forces at the end of insertion range from 17.2 mN to 43.6 mN, while maximal peak forces were observed in the range from 44.8 mN to 102.4 mN. Conclusion We hypothesize that this novel method holds the potential to assist surgeons in monitoring the insertion forces and, thus, minimizing insertion trauma and ensuring better preservation of residual hearing. Future data recording with this tool can form the basis of ongoing research into the causes of insertion trauma, paving the way for new and improved prevention strategies.